The Prevalence of Functional Disability and Associated Factors among Older People Attending Primary Health-care Centers in Riyadh City - Alhalafi, Abdullah; Al-Amoud, Maysoon; Aldahman, Reema; Abd-Ellatif, Eman; Omar, Doaa (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The burden of disability among the older population is increasing as older people grow with significant social and economic negative impacts. AIM: This study examines functional disability and its associated risk factors among older Saudi citizens attending primary health-care centers (PHCCs) in Riyadh city. METHODS: This descriptive cross-sectional study was carried out on 504 older Saudi citizens aged ≥60 years who attended a PHCC in Riyadh city between December 2019 and May 2020. Interviewer-administered questionnaire was used to assessing the disability in activities of daily living (ADL) and instrumental activities of daily living (IADL) using the Katz Index and Lawton scale. RESULTS: The prevalence of ADL and IADL disability among participants was 24.6% and 58.5%, respectively. Smoking (p = 0.019), dyslipidemia (p = 0.018), rheumatoid arthritis (p = 0.028), history of falls (p = 0.014), and an emergency visit (p = 0.049) were risk factors associated with ADL disability. Predictors of IADL disability were advanced age (p = 0.004), being female (p = 0.029), and the need for a caregiver (p = 0.000). The need for homecare was positively associated with ADL dependency (p = 0.008) and IADL dependency (p = 0.003). Furthermore, regular physical activity was a protective factor against ADL functional disabilities (p = 0.002) and IADL functional disabilities (p = 0.000). CONCLUSION: This study found a high prevalence of ADL and IADL disability among elderly Saudis. Disability was associated with several sociodemographic and health status factors. The findings of this study highlight the priority of effective and targeted preventive interventions for disability.